Laying performance and egg quality of quails supplemented with NaHCO₃ during late laying period - Rosnadir, Rosnadiana (2015)
This study was conducted on a private farm at Kampung Valdor, Pulau Pinang to evaluate and determine the effects of increased level of dietary NaHCO3 supplementation in water on egg production and egg quality parameters of quails during the late laying period. Japanese Quail (Coturnix japonica), 160 days of age, were blocked in galvanized-wire cages according to the cage locations and then assigned randomly to 3 treatment groups of hens; Treatment 0(T0) received 0% NaHCO₃ in their drinking water, Treatment 1(T1) received 0.4% NaHCO₃ in their drinking water, and Treatment 2(T2) received 0.8% NaHCO₃ in their drinking water; each treatment group consisting of 3 cages containing 10 hens. The feed fed is the commercial feed. Feed and water was given ad libitum to the hens in this experiment. The duration for this experiment was 75 days. Feed and water intake, mortality, egg production and egg weight were measured weekly. A sample of 3 eggs from each group were collected randomly every Monday for evaluation of egg quality parameters (egg weight, shape index, shell thickness, albumin index, yolk index). The results showed that the mortality rate and feed conversion ratio (FCR) were lower. The feed intake, egg production and egg weight were greater for the groups that were supplemented with NaHCO₃ in their drinking water compared with the controlled group. In conclusion, increasing NaHCO₃ level positively affected laying performance and altered the inner egg quality (albumin index, yolk index) but did not improve shell quality for late laying C. japonica. Based on Duncan Multiple Range Test for week 11mean yolk index for Group A was 20.43%, Group B was 16.53% and Group C was 17.02%. The mean of Group B and C are significantly different compared to Group A (controlled group).